Gaul undivided: Cartography, geography and identity in france at the time of the hundred years war - Serchuk, C. (Mapping Medieval Geographies: Geographical Encounters in the Latin West and Beyond, 300-1600, 2014)
Gallia est omnis divisa in partes tres. ‘All Gaul is divided into three parts.’ The opening passages of Julius Caesar’s Commentaries on the Gallic Wars define the target of Roman conquest in geographic terms. Caesar goes on to describe the boundaries of Gaul, its inhabitants, and their character. He does so – at least in part – to enhance the value and importance of his military triumph. The heirs to the vanquished Gauls – French medieval readers and translators of the Gallic Wars – consumed, copied and transformed Caesar’s text, preserving some features and emphasizing them, while erasing others. Although the text and its description of the divisions of Gaul enjoyed considerable popularity and influence in France throughout the Middle Ages, at the time of the Hundred Years War, when France was politically divided, French texts often replaced the tripartite form of Caesar’s Gaul with other models of geographical description. This essay will consider the changing character of geographical thinking about France by the French in the later Middle Ages – expressed in languages both visual and verbal. It will show how geography became entwined with contemporary French identity, particularly with reference to the ways that authors, artists and mapmakers received, transmitted and ignored the tradition of Caesar’s divided Gaul. Fought with the English, primarily on French soil, the war occasioned monumental division in France. Instigated by a dispute about the inheritance of the French crown, as well as over feudal rights owed the French king by his English rival, the Hundred Years War waxed and waned from 1337 to 1453. The calamities of the war were visited on France both physically, in terms of lost and plundered territory, and politically, in terms of the huge rifts that the war wrought in the fabric of French society. Not only did the French struggle against the English, but also, because of bickering, rivalry and ultimately murder among the peers of the realm, the French were also divided against one another, and thus the Hundred Years War also became a civil war. The Armagnacs (French supporters of the French king Charles VII), the Burgundians (French but for some critical years supporting the English) and the English divided France into three fractious parts that joined into fragile alliances. As divisions, they were not as coherent or distinct as Caesar’s provinces, but they divided France painfully if temporarily. © Cambridge University Press 2013.
Keywords: dept.art

Siate Felici: Garden imagery in a Messinese Biancheria di Letto, c. 1900 - Inguanti, Joseph J. (Embroidered Stories: Interpreting Women's Domestic Needlework from the Italian Diaspora, 2014)
For Italian immigrants and their descendants, needlework represents a marker of identity, a cultural touchstone as powerful as pasta and Neapolitan music. Out of the artifacts of their memory and imagination, Italian immigrants and their descendants used embroidering, sewing, knitting, and crocheting to help define who they were and who they have become. This book is an interdisciplinary collection of creative work by authors of Italian origin and academic essays. The creative works from thirty-seven contributors include memoir, poetry, and visual arts while the collection as a whole explores a multitude of experiences about and approaches to needlework and immigration from a transnational perspective, spanning the late nineteenth century to the late twentieth century. At the center of the book, over thirty illustrations represent Italian immigrant women's needlework. The text reveals the many processes by which a simple object, or even the memory of that object, becomes something else through literary, visual, performance, ethnographic, or critical reimagining. While primarily concerned with interpretations of needlework rather than the needlework itself, the editors and contributors to Embroidered Stories remain mindful of its history and its associated cultural values, which Italian immigrants brought with them to the United States, Canada, Australia, and Argentina and passed on to their descendants.
Keywords: dept.art